Reformulation of Criminal Justice Paradigm in 2023 Criminal Code: A Comparative Analysis of Human Rights and Islamic Legal Principles - Osamah Naufal Rahman; Risma Maulidar; Muhammad Diyaulhaq Rais (Program Studi Hukum Tata Negara, 2026)
The enactment of the 2023 Criminal Code marks a paradigm shift toward a more humane approach to punishment, one that is normatively grounded and aligned with human rights principles. This study stems from the tension between the classical retributive orientation of punishment and the global trend emphasizing corrective, rehabilitative, and restorative approaches, as well as respect for human rights. This study employs a descriptive-analytical normative qualitative method. Primary data sources include the Criminal Code and human rights instruments, while secondary data is drawn from books and journals on modern criminal justice. Modern Criminal Law is transforming into a human rights-based legal system rooted in the concept of human dignity and grounded in international human rights instruments, encompassing civil and political rights, economic, social, and cultural rights, as well as the rights of children, women, persons with disabilities, migrant workers, and the prohibition of torture. This requires continuous coordination among legal enforcers and practitioners. A human rights-based approach requires clear and empirically tested evaluative indicators to ensure the stable implementation of the law without discrimination. Reform must be accompanied by measurable and empirically verifiable evaluative parameters to ensure stable law enforcement. Ibn al-Qayyim stated that law enforcement is not only intended to punish but also to realize justice and the public good and to prevent harm. This indicates a normative alignment between modern human rights-based criminal law and the principles of Islamic law in positioning the human being as a subject whose dignity must be protected to ensure that law enforcement proceeds fairly, stably, and without discrimination.